Amount of the rice stubble on the weeds and the beans (Phaseolus vulgaris L.). - Herrera Murillo, Franklin; Agüero-Alvarado, Renán; Gamboa, Claudio (Agronomía Mesoamericana, 2003)
The assay was conducted between June 2000 and January 2001 at the Fabio Baudrit Experiment Station of the University of Costa Rica, located in the San Jose district, in Alajuela, Costa Rica. The objective of the trial was to assess the influence of 0; 1.85; 3.70; 5.60; 7.40 and 11 metric tons/ha (mt/ha) of dry matter of rice stubble (Var. CR-5272) as dead mulch on the ground surface, on the weeds and on the yield of the Huasteco bean variety, planted with least tilling. It was found that the rice stubble, in amounts over 3.7 mt/ha on the ground, drastically diminished the number of weeds, due mainly to the reduction of the temperature fluctuations and the percentage of photosynthetic active and total light that reached the soil surface. Besides, it improved the moisture holding capacity of the soil. The favorable effects of these factors were reflected in a greater production of bean grains.